SOUTH AMERICA : A 4D Book - Juarez, Christine, 1976-; Della-Rovere, Cynthia; Webber, Clare (North Mankato, Minnesota : Pebble, 2019)
Come along and investigate the continent of South America. What are its biggest cities? Where are its landforms? What languages do people speak there? Bring augmented reality to your students by downloading the free Capstone 4D app and scanning for access to awesome videos!
Includes index.
Bibliography : page 23
Keywords: Continents -- Juvenile literature; South America -- Geography -- Juvenile literature